Switching time estimation and active mode recognition using a data projection method - Hakem, Assia; Cocquempot, Vincent; Pekpe, Komi Midzodzi (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a data projection method (DPM) to detect a mode switching and recognize the current mode in a switching system. The main feature of this method is that the precise knowledge of the system model, i.e., the parameter values, is not needed. One direct application of this technique is fault detection and identification (FDI) when a fault produces a change in the system dynamics. Mode detection and recognition correspond to fault detection and identification, and switching time estimation to fault occurrence time estimation.
Keywords: switching systems; mode recognition; fault detection and isolation; data-driven method; mode discernability; switching detectability; fault identifiability